Design and testing of a controlled electromagnetic spinal cord impactor for use in large animal models of acute traumatic spinal cord injury. (September 2017) - Petteys, Rory J.; Spitz, Steven M.; Syed, Hasan; Rice, R. Andrew; Sarabia-Estrada, Rachel; Goodwin, C. Rory; Sciubba, Daniel M.; Freedman, Brett A.
Highlights: There is significant interest in large animal research for spinal cord injury for a number of reasons. There are currently no commercially available controlled electromagnetic devices for creating contusion-type SCI in large animal models. We described the initial development of a controlled electromagnetic impactor for use in large animal models. The impactor design produced consistent, reliable impacts with the acceleration necessary to produce contusion injury. Abstract: Background: Spinal cord injury (SCI) causes debilitating neurological dysfunction and has been observed in warfighters injured in IED blasts. Clinical benefit of SCI treatment remains elusive and better large animal models are needed to assess treatment options. Here, we describe a controlled electromagnetic spinal cord impactor for use in large animal models of SCI. Methods: A custom spinal cord impactor and platform were fabricated for large animals (e.g., pig, sheep, dog, etc.). Impacts were generated by a voice coil actuator; force and displacement were measured with a load cell and potentiometer respectively. Labview (National Instruments, Austin, TX) software was used to control the impact cycle and import force and displacement data. Software finite impulse response (FIR) filtering was employed for all input data. Silicon tubing was used a surrogate for spinal cord in order to test the device; repeated impacts were performed at 15, 25, and 40 Newtons. Results: Repeated impacts demonstrated predictable results at each target force. The average duration of impact was 71.2 ± 6.1 ms. At a target force of 40 N, the output force was 41.5 ± 0.7 N. With a target of 25 N, the output force was 23.5 ± 0.6 N; a target of 15 Newtons revealed an output force of 15.2 ± 1.4 N. The calculated acceleration range was 12.5–21.2 m/s 2 . Conclusions: This custom spinal cord impactor reliably delivers precise impacts to the spinal cord and will be utilized in future research to study acute traumatic SCI in a large animal.